Synthesis and Characterization of Thioxopyridine, Pyrazolopyridine and Pyridopyrazolotriazine Derivatives - ABUNADAA, N.M.; EL-LOUH, A.K.K.; AL-ZAEEM, I.S. (Asian Journal of Chemistry, 2010)
Derivatives of arylidene cyanothioacetamide (4a,b) reacted with ethyl acetoacetate to give the thioxopyridine derivatives (6a,b). Compounds 6a,b reacted with methyl iodide to yield methylthiopyridine derivatives (7a,b). Hydrazine hydrate reacted with either 6a,b or 7a,b to give aminopyrazolopyridine derivatives (8a,b). The diazonium salts of 8a,b reacted with several active methylene compounds 1, 10a-h to afford the pyridopyrazolotriazine derivatives (11-19a,b), respectively.